Menghafal Al-Qur'an sebagai syarat pernikahan dalam perspektif konstruksi sosial - Wahid, Abdurrahman (Prodi Hukum Keluarga Islam Fakultas Syari'ah Universitas Islam Zainul Hasan Genggong Probolinggo, 2024)
At the Nurul Qur'an Islamic boarding school in Kraksaan, Probolinggo, a unique local wisdom requires students to memorize 30 chapters of the Qur'an before they can marry. This practice, which lacks a theoretical or legal basis, reflects a cultural and social construction unique to the institution. This research aims to explore the social construction perspective of this local wisdom and to identify the supporting and inhibiting factors related to it. Employing a qualitative, descriptive approach, the study focuses on students at the boarding school. Data were collected through observation, interviews, and documentation, with analysis involving data reduction, presentation, and verification. The validity of findings was ensured through trustworthiness, transferability, dependability, and certainty. The study reveals that this local wisdom has been passed down through generations, rooted in social, cultural, and individual factors that align with societal norms and moral values. Supporting factors include: 1) parental involvement, 2) the Madrasatul Qur'an institution, and 3) Qur'an memorization teachers. Inhibiting factors include: 1) environmental influences such as peers who may disrupt discipline, and 2) educator-related issues like absences or illness that affect teaching consistency. The conclusion underscores that local wisdom is shaped by individual and societal factors as long as it adheres to accepted norms. The study recommends that institutions enhance systems and discipline to support students in memorizing the Qur'an, and that students adhere to institutional guidelines to meet established targets.